2011
DOI: 10.1245/s10434-011-2035-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the 1-cm Rule of Distal Bowel Resection Margin in Rectal Cancer Based on Clinical Evidence? A Systematic Review

Abstract: BackgroundDistal intramural spread is present within 1 cm from visible tumor in a substantial proportion of patients. Therefore, ≥1 cm of distal bowel clearance is recommended as minimally acceptable. However, clinical results are contradictory in answering the question of whether this rule is valid. The aim of this review was to evaluate whether in patients undergoing anterior resection, a distal bowel gross margin of <1 cm jeopardizes oncologic safety.MethodsA systematic review of the literature identified 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 32 publications
3
60
2
2
Order By: Relevance
“…Also, CRT influenced down‐staging of the tumor, and allowed sphincter‐saving operation for some patients who may have required APR 6. In addition to those aspects, shorter distal resection margin proposed by clinicopathological studies has encouraged surgeons to preserve the anus 7, 8, 9, 10, 11, 12, 13. In 1994, Schiessel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Also, CRT influenced down‐staging of the tumor, and allowed sphincter‐saving operation for some patients who may have required APR 6. In addition to those aspects, shorter distal resection margin proposed by clinicopathological studies has encouraged surgeons to preserve the anus 7, 8, 9, 10, 11, 12, 13. In 1994, Schiessel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Systematic review studies have identified a selection bias in most studies that patients subjected based on surgical decision to AR with short margin are favourable tumours than patients undergoing APR which are usually unfavourable tumours [28]. The other limitations of our study are no correction factor for bowel shrinkage was used, measurement of the extent of distal intramural spread was not performed and there was no simultaneous IOFS assessment of circumferential resection margin.…”
Section: Discussionmentioning
confidence: 91%
“…The results of our study demonstrated that patients with flattened-type tumors required a DRM of more than 20 mm from the ulcer edge in order to achieve complete cancer clearance, even when tumors had shown a favorable response to pre-CRT. On the contrary, patients with raised-type tumors required a DRM of more than 5 mm from the macroscopic tumor border, and as some researchers previously noted [15], DRM lengths <10 mm might be oncologically acceptable in some cases.…”
Section: Discussionmentioning
confidence: 96%
“…The standard distal resection margin (DRM) for LRC cases not administered pre-CRT is now set at approximately 1-2 cm [3] as a result of accumulated evidence [11,12,13,14,15], but in contrast, limited knowledge is available on adequate DRMs for LRC after pre-CRT [16,17,18]. After pre-CRT, probably since tumors frequently exhibit reduced extent of cancer and flattening of the surrounding elevated lesion [19,20], a consensus has still not been reached with regard to determination of adequate DRM, especially when the tumor has macroscopically flattened out.…”
Section: Introductionmentioning
confidence: 99%